2010
DOI: 10.1002/mds.23169
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal tracking of gait and balance impairments in cerebellar disease

Abstract: Cerebellar damage typically results in ataxia and can be caused by stroke, tumor or one of many forms of degenerative disease. Since few pharmacological options are available, most treatments rely heavily on rehabilitation therapy. Little data exist on methods for tracking the progression of ataxia, which is critical for assessing the efficacy of current and newly developing treatments. Here, we tracked the severity of ataxia, with a particular emphasis on gait and balance dysfunction, in a group of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…Gait velocity of subjects with FA was significantly slower than controls, and 6 out of 8 FA subjects walked below speeds required for community ambulation, considered faster than 0.80 m/s [22]. These results are consistent with studies reported for individuals with a variety of cerebellar ataxias [5][6][7]. Self-selected walking speed is considered a valid, reliable, sensitive and specific measure, which correlates with functional abilities, balance confidence and falls risk [22].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Gait velocity of subjects with FA was significantly slower than controls, and 6 out of 8 FA subjects walked below speeds required for community ambulation, considered faster than 0.80 m/s [22]. These results are consistent with studies reported for individuals with a variety of cerebellar ataxias [5][6][7]. Self-selected walking speed is considered a valid, reliable, sensitive and specific measure, which correlates with functional abilities, balance confidence and falls risk [22].…”
Section: Discussionsupporting
confidence: 85%
“…Studies have shown that people with cerebellar ataxia experience a gait pattern characterized by unsteadiness, reduced stride length, decreased gait velocity and increased gait variability [5,6]. The cerebellar ataxic gait pattern has been widely studied, however, the majority of these studies include subjects across age groups and with a variety of different cerebellar disorders [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical scales are often used for investigating the effect of physical therapy. In cerebellar ataxia, the most often used specific scales for the severity of cerebellar ataxia in previous studies were the scale for the assessment and rating of ataxia (SARA) [5, 10, 16, 56-59] and international cooperative ataxia rating scale (ICARS) [55,57,[60][61][62][63][64]. These scales include the measurement of not only incoordination movement of the upper and lower extremities but also balance in sitting, standing, and gait [10, 56,62].…”
Section: Evaluation For Ataxia Balance Gait Ability and Adlmentioning
confidence: 99%
“…18 The ICARS is frequently used in pharmacological studies, 20 and has 19 items in total to assess posture and gait disturbances, kinetic function, speech disorders, and oculomotor disorders. 21,22 This test takes over 30 minutes to complete, and thus a shorter version was developed, the BARS. The BARS has five items (gait, knee-tibia test, finger-to-nose test, dysarthria, and oculomotor abnormalities) resulting in a maximum score of 30 and all the items are a part of the modified international cooperative ataxia rating scale.…”
Section: Health Condition-specific Outcome Measuresmentioning
confidence: 99%